2003
DOI: 10.1097/00126334-200304010-00014
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to Antiretroviral Therapy and Persistence of HIV RNA in Semen

Abstract: Inability to adhere to therapy was strongly associated with persistent shedding of HIV RNA in semen. Measures to improve adherence are urgently needed to reduce the sexual spread of potentially drug-resistant HIV among subjects using antiretrovirals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 18 publications
2
35
0
1
Order By: Relevance
“…HIV [25,53,81] and cardiovascular disease [9,82,83]). For the vast majority of disease states, however, no such link has been made.…”
Section: Discussionmentioning
confidence: 99%
“…HIV [25,53,81] and cardiovascular disease [9,82,83]). For the vast majority of disease states, however, no such link has been made.…”
Section: Discussionmentioning
confidence: 99%
“…However, by the sixth month, optimal adherence had decreased to 39%. Optimal adherence was found to be associated with both blood and seminal HIV RNA suppression 28 . The same research group carried out a second cross-sectional study of five public health units in Rio de Janeiro and found an overall optimal adherence of 81% 29 .…”
Section: The Challenges Posed By Non-adherence To Haartmentioning
confidence: 97%
“…25 . Such discrepancies in terms of what is being measured and how it is being measured may explain the variation observed, with a range of 52 to 83% of patients considered "adherent" to ARV therapy 26,27,28,29,30,31,32,33,34,35,36,37 .…”
Section: The Challenges Posed By Non-adherence To Haartmentioning
confidence: 99%
“…Although antiretroviral drugs can greatly reduce the HIV viral load in semen, they are not foolproof in preventing HIV infection via sexual contact (2,49). A substantial percentage of HIV-positive men have active, potentially infectious viruses in their semen, even after 6 months of therapy.…”
Section: Discussionmentioning
confidence: 99%